The Politics of Smart Farming Expectations in Urban Environments - Langendahl, Per-Anders (Frontiers in Sustainable Cities, 2021)
Although farming practices are essentially situated in rural locations, they are also developing in urban environments and multiple rationalities underpin such initiatives. Urban farming practices are, among other things, recognised for their recreational and wellbeing effects (e.g. allotments) as well as to increase biodiversity and to mitigate flooding. More recently, food produced in digitally augmented and contained environments have become increasingly established in cities across the globe such as Stockholm, London and New York. These ICT enabled farming practices are different from non-smart and outdoor farming. Specifically, indoor farming practices are founded upon the view that it can produce fresh food in urban settings all year round using fewer resources (e.g. land, water, chemicals) and with reduced food miles. Since such knowledge claims may shape and structure the development and uptake of smart farming practices in urban environments they must be scrutinised. This paper begins to address this need for research by investigating the politics of smart farming expectations in relation to urban environments. Exploratory case study research was conducted on early formations of smart farming initiatives in Sweden. Drawing on the Sociology of Expectations, it explores the politics of knowledge claims embedded in smart farming initiatives at project level, and examines the performativity of these knowledge claims in envisioning more sustainable urban futures. The findings suggest that smart farming at the level of individual projects gives the appearance of change, but at the same time, it produces more of the same.